2004
DOI: 10.1583/03-1126.1
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous Laser Ablation of the Saphenous Vein for Treatment of Venous Insufficiency and Varicose Veins:Early Results From a Large Single-Center Experience

Abstract: ELAS for symptomatic saphenous vein incompetence and varicose veins has excellent short-term subjective and objective outcomes. This technique appears to be very successful in reducing symptoms, resolving varicose veins, and healing ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 18 publications
2
63
0
8
Order By: Relevance
“…First series and controlled trials reported on high clinical efficacy of endovenous therapy with low complication rates [15][16][17][18][19]. The consequences of endovenous treatment, such as venous wall thickening, a reduction in luminal diameter, thrombus formation or obliteration are currently assessed either clinically, based on duplex ultrasound findings, or on phlebography [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…First series and controlled trials reported on high clinical efficacy of endovenous therapy with low complication rates [15][16][17][18][19]. The consequences of endovenous treatment, such as venous wall thickening, a reduction in luminal diameter, thrombus formation or obliteration are currently assessed either clinically, based on duplex ultrasound findings, or on phlebography [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…24,25 A study of active ulcers showed 83% healed after EVLASER. 26 Patient satisfaction is high 26 and patients return to normal activities 25 almost immediately. No study has reported on long-term QoL changes after EVLASER.…”
Section: Endovenous Laser Treatment (Evlaser)mentioning
confidence: 99%
“…O padrão-ouro para o tratamento cirúrgico de varizes devido à insuficiência da junção safeno-femoral Cirurgia de varizes -de Medeiros CAF (JSF) associada ao refluxo na VSI é a ligadura da crossa com fleboextração [35][36][37][38] .…”
Section: Conceitos Atuaisunclassified